Roads pose a significant barrier to bee movement, mediated by road size, traffic and bee identity. Issue 6 (10th May 2021) - Fitch, Gordon; Vaidya, Chatura
Abstract: Roads are a major driver of environmental stress, yet we know surprisingly little about how roads impact the movement of insect pollinators, and consequent pollination. We investigated the influence of roads on pollinator movement and pollination by examining patterns of pigment transfer between focal plants of two species, Coreopsis verticillata and Monarda fistulosa . We asked whether roads reduced pigment transfer, and what characteristics of roads were important in driving this reduction. We also evaluated whether pollinator assemblage differed between species, and if this mediated the effect of roads on pigment transfer. Plants across a road from a pigment‐added plant received significantly less pigment than plants on the same side of the road. This effect was stronger for coreopsis than for monarda. The mean body size of visitors to coreopsis was significantly smaller than that of visitors to monarda, suggesting that smaller bees are more limited by roads. Road width was the best predictor of pigment transfer, with a smaller effect of traffic volume; further research is needed to fully disentangle the effects of different road characteristics. Roadside habitat had little influence on pigment transfer, and roadside plants did not receive significantly less pigment than plants in contiguous habitat. Synthesis and applications . This study demonstrates that roads pose substantial barriers to bee movement, reducing pollen flow between plants located across roadways from one another. Road characteristics, particularly width and traffic volume, mediated this effect, as did bee size. Our results suggest that the effects of roads on pollinators and pollination can be mitigated by many of the same design strategies currently being implemented to reduce human traffic accidents, offering the opportunity for win–win scenarios. Abstract : This study demonstrates that roads pose substantial barriers to bee movement, reducing pollen flow between plants located across roadways from one another. Road characteristics, particularly width and traffic volume, mediated this effect, as did bee size. Our results suggest that the effects of roads on pollinators and pollination can be mitigated by many of the same design strategies currently being implemented to reduce human traffic accidents, offering the opportunity for win–win scenarios.